(untitled) (Colloquia Comparativa Litterarum, 2025)
The myth about the creation of the first man has been engaging people’s minds from times immemorial to the present day. The story of the forefather, or the first man from whom the entire line of succession of human beings descends, viewed through the prism of the Old Testament has been embedded in the canvas of European literature. It can be found in many works, including in plenty of books for children. In this context, I consider he creation of Pinocchio as a variation of the creation of Adam: the marionette viewed as the alter ego of man’s forefather. Underneath the edifying story of Carlo Collodi’s wooden puppet, we can see the great myth of Adam’s existence in Eden and his banishment from Paradise. Human life in both stories is reminiscent of a mirror in which Adam’s punishment becomes Pinocchio’s reward. I follow the change in the idea of knowledge all the way through from the biblical myth to Collodi’s story about Pinocchio. The obedience to God’s commandments required of the first man is replaced in Collodi’s tale by the idea of an active and independent individual who has to make his own choices in life.